Vector Control Features by Electric Drive of Vessel Deck Mechanisms - Sultanov, E.F.; Mammadov, E.M. (Herald of Azerbaijan Engineering Academy, 2021)
The issue of control with asynchronous electric motor by vector method, passed a long way of development and widely applied in modern electric drives of alternating current is being discussed in article. This method provides the simplicity and efficiency in control, considered as a complex object of asynchronous motor with short-circuited rotor. Spheres of applying the vector method always expand and the applying of it in automated electric drives, contributes of replacement and displacement of electric drive of constant current. Among the factors, first of all contributing as widely applying of asynchronous electric drives by vector control, beginning from 70s of XX century, is possible to indicate the development of powerful electronics, providing the issue of reliable and economically beneficial converters as well as the development of quickly affected microelectronics capable to decide the complex algorithms of control. In the case of sharp growth of the resistance moment on a shaft of electric engine during the operation of the ship deck mechanism due getting the necessary speed reduction on the working mechanical feature (soft mechanical feature M w=const) is possible by applying vector method of regulation. At this, the necessary providing of limit and smoothness becomes easier of electric drive speed regulation. The features of vector control by asynchronous electric motor applied in ship electric drives were researched and offered the conception by vector control asynchronous electric motor in automatic systems in ships with symbol class of automation AUT 2.